Performance of Broiler Chicken that Gives Ration Containing Fermentation of Catfish Waste (Clarias sp.) Using Red Guava MOL (Psidium guajava L.) - Dini Widianingrum; R. Somanjaya; O. Imanudin (Fakultas Peternakan, Universitas Padjadjaran, 2018)
The research was conducted at Faculty of Agriculture Laboratory Majalengka University. The objective of the research was to get the level use of catfish waste as a source of animal protein in broiler chicken rations. This reseach uses a completely randomized design (CRD) with four treatments R0 (0%), R1 (8%), R2 (16) and R3 (24%) waste catfish and each treatment was repeated five times. Observed variables were body weight increase, feed consumption and feed conversion. The results showed that the use of fermented catfish waste as much as 16% in the ration resulted in the best performance of broiler chickens, namely body weight gain 1097.75 grams, ration consumption 2143.75 grams, and conversion ration 1.95.